INVESTIGATION OF THE DYNAMICS OF ANXIETY IN PATIENTS WITH TEMPOROMANDIBULAR JOINTS DISKS DISLOCATION AND EVALUATION OF THE EFFECTIVENESS OF ORTHOPEDIC TREATMENT OF THESE PATIENTS - S. V. Beinarovich (Кубанский научный медицинский вестник, 2018)
Aim. To study the dynamics of the anxiety state in patients with temporomandibular joint (TMJ) join disks dislocation and the effectiveness of conservative treatment in terms of the quality of life of these patients.Materials and methods. The state of anxiety in patients with dislocations of the TMJ joint discs was studied using a Spielberger questionnaire. The efficacy of conservative complex orthopedic dental treatment of these patients was assessed using the OHIP-49 questionnaire (Slade, G.D., Spencer, A.J. Oral Health Impact Profile, 1994). The data wasprocessed using the program "STATISTICA 6.0" and "Microsoft Office Excel".Results. It has been revealed that in patients with dislocations of the joint discs of the TMJ, the level of anxiety is higher than in those who have no signs of the TMJ dysfunction. In patients with signs of uncontrolled dislocation of the joint meniscus, the level of anxiety is higher than in people with other forms of TMJ dysfunction. A high level of personal anxiety persists after dental treatment and can become one of the main causes of relapses of TMJ dysfunction. The OHIP-49 index has revealed deterioration in the quality of life in patients with dislocations of the joint discs of the TMJ. It should be noted that in patients with uncontrolled dislocations of the joint menisci, deterioration in the quality of life is more pronounced.Conclusion. Thus, the proposed conservative orthopedic dental treatment can improve the quality of life of patients with dislocations of the joint discs of the TMJ and reduce the level of situational anxiety n these patients.